A legal study on monarchy system in Malaysia: a comparative with India and United Kingdom / Nor Nabilah Arippin … [et al.] - Arippin, Nor Nabilah; Abd Hadi, Annur Atiqah; Abd Halim, Amiera; Said, Nur Sazarina (Faculty of Law, 2011)
This study, "A Legal Study on Monarchy System in Malaysia: a Comparative with India and United Kingdom", is completed as a fulfillment of the course of Bachelor of Legal Studies (Hons). This study was mainly conducted in Shah Alam and Kuala Lumpur to look into the main reasons why the public question the position of the Monarchs and the Yang di-Pertuan Agong in the present day and a comparison is made between India and United Kingdom. There are several methods used in order to find answers and to collect facts to answer the research questions and to meet the objectives of the study. Qualitative research which is library-based was conducted to gather information and relevant data in this study. The relevant data was gathered from various text books, journals, and articles both from the shelves and on the internet. The searchers have conducted interviews with an individual well-versed in the relevant area of constitutional law that is Madam Nurnazida Binti Nazri who is a lecturer of Faculty of Law in University Technology of Mara; in obtaining a clearer insight on the topic. Apart from that, the researchers have also provided the comparison of the Monarchy system with United Kingdom and it's non-existence in India's government. These project papers touch on laws and its components. We have included our recommendation and conclusion at the end of our project paper which we hope it will help to put to rest the situation regarding this issue.